A new methodical approach in neuroscience: assessing inter-personal brain coupling using functional near-infrared imaging (fNIRI) hyperscanning - Scholkmann, Felix; Holper, Lisa; Wolf, Ursula; Wolf, Martin (Frontiers in Human Neuroscience, 2013)
Since the first demonstration of how to simultaneously measure brain activity using functional magnetic resonance imaging (fMRI) on two subjects about 10 years ago, a new paradigm in neuroscience is emerging: the assessment of the inter-brain coupling between two or more subjects, termed “hyperscanning”. The hyperscanning approach has the potential to enable a new view on how the brain works and will reveal as yet undiscovered brain functions based on brain-to-brain coupling, since the single-subject setting cannot capture them. In particular, functional near-infrared imaging (fNIRI) hyperscanning is a promising new method, offering a cost-effective, easy to apply and reliable technology to measure inter-personal interactions in a natural context. In this short review we report on fNIRI hyperscanning studies published so far and summarize opportunities and challenges for future studies.